Ultrasound-Triggered Release And Cellular Uptake Of Trastuzumab-Conjugated Immunoliposomes Targeting Breast Cancer - Amal Ahmed, Ghaleb Husseini, and Rana Sabouni (International Journal of Advanced Science and Technology, 2020)
Conventional treatment for cancer has many side effects that limited its use. This augments the need for new smart drug delivery systems, which are nanocarriers that can shield the healthy cells from the adverse side effects of chemotherapy and enhance the drug's pharmacokinetics. One type of biodegradable nanocarriers is liposomes. Once these drug-loaded liposomes reach the tumor, their release can be triggered using ultrasound, an external modality capable of accelerating the cytotoxic effects of the drug and subsequent accumulation inside tumor cells. The purpose of this study is to test the ultrasound-triggered release and cellular uptake of immunoliposomes that have an increased affinity toward breast cancer cells. Proteins attached on the surface of the liposomes will guide them to the tumor that overexpresses receptors for that protein. First, the attachment is confirmed, then ultrasound triggered release is studied.